The coalface of journalism: A qualitative research investigation into development communication objectives amongst rural newspapers in the Overberg District - Galant, Raashied (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Journalism))--University of Stellenbosch, 2010.